Associations Between Early Life Stress and Gene Methylation in Children. Issue 1 (24th July 2014) - Romens, Sarah E.; McDonald, Jennifer; Svaren, John; Pollak, Seth D.
<x xml:space="preserve">Abstract</x> Children exposed to extreme stress are at heightened risk for developing mental and physical disorders. However, little is known about mechanisms underlying these associations in humans. An emerging insight is that children's social environments change gene expression, which contributes to biological vulnerabilities for behavioral problems. Epigenetic changes in the glucocorticoid receptor gene, a critical component of stress regulation, were examined in whole blood from 56 children aged 11–14 years. Children exposed to physical maltreatment had greater methylation within exon 1F in the NR3C1 promoter region of the gene compared to nonmaltreated children, including the putative NGFI‐A (nerve growth factor) binding site. These results highlight molecular mechanisms linking childhood stress with biological changes that may lead to mental and physical disorders.